Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Pembelian Nasi Krawu Habbah Sufa - ., Mukminatin; Djazuli, Raden Achmad (CV.ITTC INDONESIA, 2025)
Nasi Krawu Habbah Sufa is a restaurant founded by the son of Hj. Sufayyah (Mbuk su) known as the first pioneer to serve Nasi Krawu in Gresik Regency. Gresik Regency has a large number of Nasi Krawu sellers, which creates competition between companies. Many economic actors currently have difficulty understanding consumer interests because of the many factorsothat toodetermine trend Nasi Krawu sales and consumer characteristics when buying Nasi Krawu, as well as when buying Nasi Krawu Habbah Sufa in Gresik Regency. The survey was conducted at the Nasi Krawu Habbah Sufa restaurant from October to Decembero2023. Data collectionoin. Sample size with a total. Based on survey development trend Nasi Krawu Habbah Sufa has experienced an increasing trend in sales over the past five years, and the consumer age group of 30-39 years contributed 40% and was the majority. In terms of gender, 68% of respondents were female, 39% of respondents had the highest level of education of S1 (S1 Sarjana), and most respondents were domiciled in Kab. Gresik percentage of 79%, the respondents' workplaces were dominated by private employees percentage of 31%, respondents' income ranged from Rp3,000,000 to Rp4,999,999 per month, percentage of 44%, Respondent frequency of Nasikura purchases often, 3 to 5 times a day month, with a share of 48%. Based on the results of the analysis, it shows that: (1) While the variables of price, product quality, location, service quality, and income have a significant influence on purchasing decisions. (2) In some cases, the variables of product quality and service quality have a significant influence on purchasing decisions, while price, location.